2021
DOI: 10.1001/jamanetworkopen.2021.35271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Artificial Intelligence–Augmented Digital System for Histologic Classification of Colorectal Polyps

Abstract: This diagnostic study evaluates the accuracy and assessment time of an artificial intelligence (AI)–augmented digital system compared with standard microscopic assessment for interpretation of slides with colorectal polyp samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…Deep neural networks have been proved a powerful tool in computer vision and are increasingly applied in medical image analysis [15][16][17] . In the histologic image inference domain, deep convolutional neural networks are applied as a backbone for whole-slide image analysis and classification 18,19 .…”
Section: Deep Convolutional Neural Networkmentioning
confidence: 99%
“…Deep neural networks have been proved a powerful tool in computer vision and are increasingly applied in medical image analysis [15][16][17] . In the histologic image inference domain, deep convolutional neural networks are applied as a backbone for whole-slide image analysis and classification 18,19 .…”
Section: Deep Convolutional Neural Networkmentioning
confidence: 99%
“…The computer aided diagnosis systems can ease this labor-intensive work and minimize the mistakes of the traditional approaches. Therefore, employing a computer aided diagnosis system, in which differentiation of non-adenomatous and adenomatous biopsies is automated, would be beneficial [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DL based approaches are actively employed for pattern classification or analysis of the medical images. There are extensive studies conducted with numerous methods focusing on the individual diagnosis of colorectal cancer from histopathology images, such as classification of colorectal adenocarcinoma [ [2], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15]], colon polyp classification [ [16], [17], [4], [18], [19], [20], [21]] and colon gland classification [ [5], [22], [23]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the use of AI improved the accuracy of 4-class differentiation of pathologic diagnoses from 74% to 81%. 13 The combined use of semisupervised learning and AI-aided pathologic diagnosis may be the best solution to overcome this problem.…”
mentioning
confidence: 99%